Austenite reversion kinetics and stability during tempering of an additively manufactured maraging 300 steel - Conde, F. F.; Escobar, J. D.; Oliveira, J. P.; Jardini, A. L.; Bose Filho, W. W.; Avila, J. A. [UNESP] (Elsevier, 2019)
Reverted austenite is a metastable phase that can be used in maraging steels to increase ductility via transformation-induced plasticity or TRIP effect. In the present study, 18Ni maraging steel samples were built by selective laser melting, homogenized at 820 °C and then subjected to different isothermal tempering cycles aiming for martensite-to-austenite reversion. Thermodynamic simulations were used to estimate the inter-critical austenite + ferrite field and to interpret the results obtained after tempering. In-situ synchrotron X-ray diffraction was performed during the heating, soaking and cooling of the samples to characterize the martensite-to-austenite reversion kinetics and the reverted austenite stability upon cooling to room temperature. The reverted austenite size and distribution were measured by Electron Backscattered Diffraction. Results showed that the selected soaking temperatures of 610 °C and 650 °C promoted significant and gradual martensite-to-austenite reversion with high thermal stability. Tempering at 690 °C caused massive and complete austenitization, resulting in low austenite stability upon cooling due to compositional homogenization.
Keywords: Additive manufacturing; Maraging 300; Martensite-To-Austenite reversion